Semantic Analysis Of Islamic Diction In Contemporary Prophetic Literature As A Basis For Extraction Of Indonesian Teaching Materials In The Independent Curriculum - Habiburrahman Habiburrahman; Masri’ah Masri’ah; Laili Amalia (Molang: Journal Islamic Education, 2026)
The withdrawal of Indonesia's Literature in Curriculum guidebook (Keputusan Mendikbudristek No. 025/H/P/2024) following controversy over explicit content exposes a structural gap: the absence of a linguistically grounded, replicable instrument for vetting literary texts — a gap most consequential for Islamic prophetic literature, which dominates Indonesian public readership yet remains vulnerable to dogmatic misreading when its Arabic-rooted diction is taken at face value. Using an Exploratory Sequential Design, this study applied Jost Trier's Semantic Field Theory and Eugene Nida's Componential Analysis, framed by Kuntowijoyo's Prophetic Literature philosophy, to corpora by Asma Nadia, Habiburrahman El Shirazy, and Lusi Rahmalia; from 312 extracted lexemes, 60 purposive tokens meeting dual inclusion thresholds (frequency ≥ 3; verified contextual deviation from KBBI) were subjected to componential analysis, with inter-rater reliability established through double independent coding (Cohen's κ = 0.84). Islamic diction was found to distribute non-randomly into three semantic fields — exoteric worship, esoteric affection, and socio-liberative relations — each mapping to one of Kuntowijoyo's prophetic pillars; most radically, the re-semantization of jihad suppressed the feature [+Militaristic] while injecting [+Feminist Liberative Agency] and [+Intellectuality], restoring the root jahada to its emancipatory etymology, while componential analysis further identified four categories of semantic-register deviation in a negative comparison corpus, demonstrating its diagnostic utility beyond ideological analysis. These findings establish componential semantic mapping as an objective, reproducible curation standard for prophetic literature in national curricula, operationalised through an ADDIE-based interactive e-book prototype that functions as a classroom close-reading instrument for context-sensitive literary education in Indonesia.